Pemanfaatan Alat Peraga Sederhana untuk Meningkatkan Penguasaan Konsep IPA Siswa Kelas IV SD Negeri Beber - Hikmawati Hikmawati; Zulfan Zulfan; Siti Aminah (Unram Journal of Community Service, 2023)
The purpose of this community service activity is to improve the mastery of science concepts for fourth grade students of SD Negeri Beber through the use of simple teaching aids. The activity was carried out in class for 2 meetings, namely 27 August 2022 and 10 September 2022, located at SD Negeri Beber, Batukliang, Central Lombok, NTB. The number of participants who took part in the activity was 25 students. The method of activity starts from preparation, implementation, and evaluation. In the preparation stage, the team prepares simple teaching aids that will be used in learning, including learning tools, namely the Learning Implementation Plan (RPP), teaching materials, student worksheets (LKPD), and assessment instruments. At the implementation stage, the team conducted learning using simple teaching aids and other learning tools. At the evaluation stage, the team reflected on the learning. The simple teaching aids used in this activity are science teaching aids for the concept of sound and energy sources. The results of the activity show that the average value of mastery of science concepts at the first meeting is 86.2 with a percentage of learning completeness of 87%, while at the second meeting the average value of mastery of science concepts is 94.3 with a percentage of learning completeness of 94%. Thus, it can be concluded that the use of simple teaching aids can improve the mastery of science concepts for fourth grade students of SD Negeri Beber